The Effect of Price and Product Quality on Repurchase Intention Through Customer Satisfaction as an Intervening Variable - Dera Reggiana; Nurul Hermina (Dinasti International Journal of Education Management And Social Science, 2025)
The focus of this research is to measure the impact of price and product quality on repeat purchase intention through customer satisfaction as an intervening variable. The population of this study was Shopee sellers who have used Shopeasytools for at least one month. The study employed a quantitative methodology and purposive sampling as a technique to determine the sample. The researcher determined 100 Shopeasytools users as respondents in this study. Smart PLS and structural equation modeling (SEM) were utilized to examine the theoretical model proposed. The bootstrapping method is utilized to examine the hypothesis and the mediating role of customer satisfaction. The results showed that repeat purchase intention is positively and significantly affected by price and product quality. Furthermore, Indirect research findings indicate that the effect of price on repurchase intentions is positively and significantly mediated by customer satisfaction as an intervening variable. In addition, repurchase intention is positively and considerably mediated by customer satisfaction as an intervening variable, which in turn fully explains the influence of product quality. The importance of customer satisfaction in determining repurchase intention is highlighted by this finding. A good price point coupled with high product quality is likely to enhance customer satisfaction, subsequently motivating consumers to engage in repeat purchases from Shopeasytools.